Alteraciones vergenciales y su relación con la habilidad de lectura y escritura en niños del Rcto. Matecito, Febres Cordero - Los Ríos, noviembre 2023 - abril 2024 - Bravo Sellan, Joisce Leonela (2024)
Vergencial impairments play a transcendental role in the learning of all reading and writing skills, since these skills are based on motor responses that come into play for the respective comprehension of letters and words. If the infant does not visually discriminate the patterns to be duplicated and those to be expressed, this will have direct consequences on the learning of these skills. The objective of the current project was to determine the relationship of visual impairments with the development of reading and writing skills in children. The present study had as population the children inhabitants of Rcto. Matecito of the Febres Cordero parish, from 6 to 11 years of age, who entered this study through a non-probabilistic sampling, and at the convenience of the researchers, the beneficiaries were children who before accessing the study were presented with an informed consent that was communicated and signed by each of their legal guardians, responsible for the children, prior to the study, The sample of 40 children was obtained and all the optometric examinations were carried out in a timely and complete manner, with emphasis on the evaluation of the vergencial system and with the help of a collaborating teacher who was knowledgeable about the study. (TA.L.E) to observe the levels of reading and writing skills. By means of the optometric evaluation and data processing, it was possible to verify that there is a relationship between the variables described in this study.